Theoretical modeling expressions for networked enzymatic signal processing steps as logic gates optimized by filtering. Issue 1 (2nd January 2017) - Privman, Vladimir
Abstract: We describe modeling approaches to a 'network' of connected enzyme-catalyzed reactions, with added (bio)chemical processes that introduce biochemical filtering steps into the functioning of such a biocatalytic cascade. Theoretical expressions are derived that allow simple, few-parameter modeling of processes concatenated in such cascades, both with and without filtering. The modeling approach captures and explains features identified in earlier studies of enzymatic processes considered as potential 'network components' for multi-step information/signal processing systems.